Penggunaan Media Flash Card Hijaiyah Terhadap Kemampuan Membaca Al-Qur’an di SMP PAB 5 Patumbak - Siti Nurfadillah; Juli Maini Sitepu (Jurnal Penelitian dan Ilmu-Ilmu Keislaman, 2023)
This research aims to determine the effect of using hijaiyah flash card media on the ability to read the Al-Qur'an. The research method used is quantitative, quasi-experimental research. The subjects of this research were students in class VIII-3 as the experimental class and VIII-5 as the control class. The data collection techniques used were Al-Qur'an reading tests, observation, interviews and documentation. The data analysis used was the independent sample t-test. Based on the results of data analysis using the independent sample t test, it was obtained that the sig(2-tailed) value was smaller than 0.05 (0.000 < 0.05) as Ho was rejected and Ha was accepted. The result of the average number of the experimental class was 85,66 while the result of the average number of the control class was 67,16.This shows that there are difference in students ability to read the Al-Qur’an using hijaiyah flash card media and iqro media so it can be concluded that the use of hijaiyah flash card media has an effect on the ability to read the Al-Qur'an at SMP PAB 5 Patumbak